MECHANISM FOR ASSESSMENT OF FACTORS AFFECTING THE DEVELOPMENT OF SMALL BUSINESS SUBJECTS - Israilov, Rusrambek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Abstract. Small business and private entrepreneurship is an integral element of the mechanism of the modern economy, so its research is very relevant today. At the current stage of the development of the world economy, small business and private entrepreneurship face many obstacles: in underdeveloped countries - insufficient support from the state or its ineffectiveness; problems in developed countries are not so much dependent on internal factors as external, for example, the current state of the world economy. Small business and private entrepreneurship offer innovative ideas in the field of climate change, resource efficiency, social cohesion and contribute to the transition of countries to a sustainable and digital economy. In some developed countries, the result of its activity is more than half of the annual GDP. The main part of the economically active population is engaged in this type of business. Such a result is ensured not only by the state's favorable conditions for the implementation of business activities, but also by the responsibility of small business and private business entities, the honesty and transparency of their activities.